1997
DOI: 10.1128/mcb.17.9.4948
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocyte Nuclear Factor 1α Gene Inactivation Impairs Chromatin Remodeling and Demethylation of the Phenylalanine Hydroxylase Gene

Abstract: Hepatocyte nuclear factor 1 ␣ (HNF1␣) is a homeoprotein that is expressed in the liver, kidney, pancreas, and digestive tract. Its inactivation in mouse resulted in decreased transcription of known target genes such as albumin and ␣ 1 -antitrypsin. In contrast, the phenylalanine hydroxylase (PAH) gene was totally silent and unresponsive to normal inducers like glucocorticoids and cyclic AMP in the liver. DNase I and micrococcal nuclease digestion of liver nuclei showed that HNF1␣ inactivation had drastic effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 49 publications
1
69
0
Order By: Relevance
“…We included global transcriptional coactivator p300 because HNF-1α has been reported to control chromatin remodelling [21,22] by the recruitment of coactivators possessing intrinsic histone acetytransferase activities such as p300 [23] or its homologue, cAMP-response element-binding protein(CREB)-binding protein (CBP) [24]. p300 or CBP also acts as a molecular bridge between transcriptional factors by binding to the activation domain of some transcriptional factors such as CREB as well as multiple components of the basal transcriptional machinery including RNA polymerase II complex [24].…”
Section: Discussionmentioning
confidence: 99%
“…We included global transcriptional coactivator p300 because HNF-1α has been reported to control chromatin remodelling [21,22] by the recruitment of coactivators possessing intrinsic histone acetytransferase activities such as p300 [23] or its homologue, cAMP-response element-binding protein(CREB)-binding protein (CBP) [24]. p300 or CBP also acts as a molecular bridge between transcriptional factors by binding to the activation domain of some transcriptional factors such as CREB as well as multiple components of the basal transcriptional machinery including RNA polymerase II complex [24].…”
Section: Discussionmentioning
confidence: 99%
“…The HNF1␣ target gene, pah, encoding the protein phenylalanine hydroxylase (PAH) (15) was not expressed in HCA nodules (SI Fig. 5J), but was expressed in normal liver, hyperplastic and dysplastic foci, and HCC nodules (SI Fig.…”
Section: Distinct Pathways Of Tumorigenesis In Met Transgenicmentioning
confidence: 99%
“…The study of the phenotype of mice carrying mutations in these genes has shown that Hnf1a and b play important roles in the function and/or differentiation of epithelia. In fact, Hnf1a-deficient mice (Hnf1a -/-) are born normally, but suffer from hepatic, pancreatic and renal functional defects (Pontoglio et al, 1996;Pontoglio et al, 1997;Pontoglio et al, 1998;Lee et al, 1998;Pontoglio et al, 2001). By contrast, germ-line Hnf1b-deficiency is embryonic lethal because of defective differentiation of extra-embryonic visceral endoderm (Barbacci et al, 1999;Coffinier et al, 1999).…”
Section: Introductionmentioning
confidence: 99%